2013
DOI: 10.1177/1934578x1300800125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypogymnia physodes Extracts and their Depsidones on Micronucleus Distribution in Human Lymphocytes

Abstract: Three lichen depsidones, physodalic acid (1), physodic acid (2), and 3-hydroxy physodic acid (3), were isolated from Hypogymnia physodes diethyl ether extract using column chromatography, and their structures determined by comparing their UV, 1 H and 13 C NMR spectroscopic and MS data with those given in the literature, as well as with data computed by CHEM draw ultra 11 software. The contents of 1, 2 and 3 were determined in the methanol (ME), acetone (AE), and diethyl ether (EE) extracts using reversed-phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Cytokinesis - block micronucleus assay was performed as previously described (Fench and Morley, 1993[ 7 ]; Stojanović et al, 2013[ 25 ]). The cell culture lymphocytes were treated with 1.0, 2.0 and 3.0 μg mL -1 of the examined acetone extracts.…”
Section: Methodsmentioning
confidence: 99%
“…Cytokinesis - block micronucleus assay was performed as previously described (Fench and Morley, 1993[ 7 ]; Stojanović et al, 2013[ 25 ]). The cell culture lymphocytes were treated with 1.0, 2.0 and 3.0 μg mL -1 of the examined acetone extracts.…”
Section: Methodsmentioning
confidence: 99%
“…This compound also diminished the proliferation of thymocytes inducing cytotoxicity via ROS production. Physodalic acid reduced the frequency of micronucleus (30.3 %) on lymphocytes [71,104].…”
Section: Physodalic Acidmentioning
confidence: 95%
“…Moreover, physodic acid reduced thymocyte proliferation-induced cytotoxicity via oxidative stress mainly through ROS production [71]. On lymphocytes, this depsidone significantly decreased micronucleus frequency (28.2 %) compared to the positive control [104]. Furthermore, this compound proved to significantly reduce human cancer HeLa cell viability (IC 50 [24 h] value of 171 μg/mL and IC 50 [72 h] value of 63 μg/ mL) [105].…”
Section: Physodic Acidmentioning
confidence: 99%
“…Our previous paper [3] showed that lichen depsidones, physodalic acid, physodic acid, and 3-hydroxy physodic acid, also decreased the frequency of MN at a concentrations of 1.0 and 2.0 µg/mL more than amifostine at a concentration of 1 µg/mL. However, their effects were smaller than the effect of usnic acid.…”
mentioning
confidence: 90%
“…Continuing our investigation on the biological activities of the lichen substances [2,3], herein we report the clastogenic effect (micronucleus distribution) and antiproliferative effect (CBPI) in peripheral blood lymphocytes of the atranorin (isolated from Hypogymnia physodes), evernic acid (isolated from Evernia prunastri), and (+)-usnic acid (isolated from Usnea barbata). The structures of examined compounds 1, 2, and 3, as well as structures of positive control (amifostine) and negative control (mitomycin C, MMC) are given on Figure 1.…”
mentioning
confidence: 93%